Characterization of breed additive and heterosis effects in beef cattle using experimental results - Theunissen, Anette (University of the Free State, 2011)
The objective of this study was to infer direct and maternal additive effects and direct and maternal heterosis effects for growth, fitness and carcass traits in beef cattle using least squares means estimated from crossbreeding studies by Els (1988) and De Bruyn (1991). The dataset was formed by recording each least squares mean along with the breed composition, maternal breed composition and direct and maternal heterozygosity. Each trait was analyzed using a single trait fixed effect model which included source of data as a fixed effect and breed composition and heterozygosity as covariates. Breed solutions were relative to the Afrikaner breed. Heterosis results were also obtained for crosses not made. Among breed groups, crossbred calves showed higher average values for almost all traits than purebred calves. The average direct heterosis contributions to weight traits in ten two-breed genotypes, which involved the Afrikaner (A) as dam line and the Simmentaler (S), Brahman (B), Charolais (C) and Herefords (H) as sire lines were 3.5, 7.9, 8.2 and 4.3% for birth weight (BW), weaning weight (WW), 19-month heifer weight (HW) and cow weight at partus (CW) respectively. Similarly, the average maternal heterosis effects for the weight traits in the four A crossbred dam genotypes (BA, CA, HA and SA) were 1.5, 8.8, 4.9 and 2.9% for the growth traits respectively. Due to additive and non-additive effects of C and B purebreds on BW these sires should only be bred to mature cows. For a weaner calf production system, the C genotype had the highest direct breed effect of +64.1 kg or 34.8% for WW. The combined additive effect of the C dam line was however, exceeded by the S dam line (+38.4 kg or +20.9% versus +50.0 kg or +27.2%). The total combined heterosis effect of the CA dam line was +32.5 kg versus the +19.2 kg effect of the SA dam line. The average expected phenotypic values for WW for the SA dam line was thus larger than the CA dam line (233.3 versus 230.7 kg). The maternal heterosis effect of the HA dam was the second largest (+22.1 kg) of the four two-breed combinations of A. The B genotype used in the study did not have a true superior ability to increase the expected WW in the A breed. The direct and maternal heterosis effects of the breed were - 0.5 kg or -0.3% and +22.1 kg or 12.0% respectively. The H breed had the lowest direct breed effects of +24.7 kg or +13.4% on WW out of the four purebred sire lines that were bred to the A dam line and a small negative direct heterosis effect (-0.5 kg or -0.3%). Furthermore, the maternal additive effect was negative (-29.6 kg or -16.1%). The maternal heterosis effect however, was positive (+22.1 kg or +12.0%). The A sire line had the lowest expected phenotypic values for HW and CW (323.9 and 434.3 kg respectively), indicating that these heifers would probably reach puberty earlier and that these cows would be smaller compared to genotypes from S, B, C and H genotypes. On average two-breed genotypes had 48.9 and 40.6 kg expected increase in HW and CW respectively, and an additional 21.9 kg and 20.4 kg for the two traits respectively in threebreed genotypes (backcrossing excluded). The H sire line did not have a true ability to increase expected CW in the A breed. The C genotypes had the lowest average individual heterosis effect of -17.6 kg (-4.0%) on CW of all four sire lines which were involved in the ten different two-breed combinations of the study. However, the CA dam line was responsible for the highest maternal heterosis effect of +54.8 kg or +12.6% out of the four crossbred A dam lines. By utilizing genotypic differences the opportunity for high productivity and profitability can be maximized, especially through cumulative traits such as the calf/cow weight ratio. All crossbred genotypes, except the BA genotype, increased the calf/cow weight ratio. Results indicated that the A breed should constitute 75% of the genetic make up of B and C crossbred genotypes and 25% of H and S crossbred genotypes to maximize calf/cow weight ratios. The HSA, HBA and BSA, genotypes had the largest calf/cow weight ratios of 0.509, 0.506 and 0.495 respectively, mainly due to the large direct heterosis effects of +22.7 (+12.3%), +28.0 (+15.2%) and +36.7 kg (+19.9%) of the HS, HB and BS genotypes for WW respectively. This gives opportunity for direct paternal heterosis to be used in crossbreeding systems with purebred A dams. Alternatively, since the B breed had a true ability to increase the expected BW in the A dam, it is suggested that a specific or rotational crossbreeding system which involves S and A dams that are mated with either H or B (only on mature dams) sires for the production of weaner calves under sweet veld conditions, be used. The data were also used to estimate the additive and non-additive effects for fitness traits in the two- and three-breed crosses. The average direct heterosis contributions were +14.9, +109.1, -162.7, +21.0 and 15.4% respectively for CR, MB, MP, WP and WR for ten two breed genotypes. Similarly, the average maternal heterosis effects in four A crossbred dam genotypes were 0.0, -87.5, +97.7, -1.9 and -7.4% for the fitness traits respectively. The HA genotype had the highest expected F of 83.1% in two-breed genotypes. The direct heterosis contributions in the HA genotype were +21.7, -2.3, -5.8, +28.3 and +30.1% percentage units respectively and the maternal contributions were -8.2, -2.4, +1.6, -6.4 and -11.6 for the traits respectively. The expected phenotypic values for improved traits in the HA and AHA genotypes were 94.9 versus 96.4% for CR, 92.2 versus 96.3% for WP and 83.1 versus 86.8% for WR (MB and MW remained unchanged). Crossbreeding the A dam line with the B sire line resulted in improved expected WR: 66.7 versus 80.2% in BA. Backcrossing the BA genotype decreased WR. This could mainly be explained by the increased expected MW; 3.3% in the A versus 6.0 and 15.6% in the BA and ABA genotypes respectively and the lower expected WR of 72.8 and 74.5% in the ABA and BBA genotypes respectively. While the SA genotype had an improved expected WR of 78.4% compared to the A genotype (66.7%), the WR in the ASA progeny was the lowest of all genotypes (60.4%). The low expected WR of the SA genotype could be explained by the increased expected MB of 5.3 versus 2.2% and MW 5.7 versus 3.3% of the A breed. The poor performance of the SSA genotype could be ascribed to an increase in MB and MW which was 7.3 and 4.3% respectively. The ACA, AHA and BHA genotypes had the highest expected WR of 86.9, 86.8 and 83.0% respectively. A specific crossbreeding combined with a terminal sire system is suggested to increase fertility in the A breed. Rotational systems will not have the same advantage since backcrossing the CA or HA dams to their respective sire lines would decrease the WR to 64.2 and 73.1% respectively. Alternatively, CA, HA or CH crossbred sires could be used on purebred A dams in a specific crossbreeding system. These genotypes had the largest direct heterosis effect on WR of all ten two-breed genotypes (36.5, 30.1 and 30.8% percentage units respectively). In a specific two-breed system the HA genotype would maximize WR. Although the average direct heterosis effects were unfavourable (-2.1 and -13.0 g/day respectively) for feedlot gain (FG) and carcass gain CG), feed conversion ratio (FCR) was -2.3% (a desirable effect). The average maternal heterosis effects for the feedlot traits were undesirable in the four A crossbred dam genotypes (-1.3, -7.4, and +0.9% respectively) for all the traits. Although these average heterosis effects suggest that feedlot traits do not benefit from crossbreeding, selected genotypes offer opportunity to increase feedlot production efficiency. As purebred the A compared less favourably in feedlot traits with Bos taurus breeds. However, it was evident that the A dam in two-breed crossbreeding could outperform the purebred S and Bos taurus crossbred dam lines in most of the these traits. The average direct heterosis contributions to feedlot traits in ten two-breed genotypes for the S, B, C and H as sire lines were -2.1, -13.0 (undesirable) and -2.3% (desirable) for feedlot gain (FG), carcass gain (CG) and feed conversion rate (FCR) respectively. Similarly, the average maternal heterosis effects for the feedlot traits in the four A crossbred dam genotypes were -1.3, -7.4, and +0.9% (undesirable) for FG, CG and FCR respectively. However, the A dam could be utilized in two-way crossbreeding systems with a terminal sire such as the C. The CCA genotype had expected average FG, CG and FCR of 1376.8 g/day, 781.2 g/day and 6.0 kg/kg respectively. Alternatively, the paternal heterosis contributions from BA, HA, SA, BH, BS and HS sire lines were also favourable. The aforementioned genotypes could thus be used as sire lines on purebred A dams to improve feedlot traits. It should however be noted that the data did not take cogniance of the genetic trends in the traits and the effects on heterosis parameters in any of the breeds since the conduction of the crossbreeding experiments. Heterosis units are therefore not directly applicable.
Dissertation (M.Sc.Agric. (Animal, Wildlife and Grassland Sciences))--University of the Free State, 2011
Keywords: Beef cattle -- Hybridization; Beef cattle -- Breeding; Beef cattle -- Genetic engineering; Beef cattle -- Carcasses; Heterosis; Terminal sire; Specific two- and three-breed crossing systems; Paternal heterosis; Fitness traits; Feed conversion ratio; Weaning rate; Growth traits; Crossbreeding parameters; Carcass traits; Afrikaner cattle; Calf/cow weight ratio